APPLICATION OF BESSEL EQUATION TO CIRCULAR SLIT FRAUNHOFER DIFFRACTION: A SYSTEMATIC REVIEW - Nasiroh, Anisa Qoriq Atun; Lira, Lira; Sari, Intan Purnama; Akhsan, Hamdi (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
This article aims to introduce the development of a simulation model using matlab in the calculation of the bessel function to describe the fraunhofer diffraction pattern in a circular slit. This research method uses the Systematic Literature Review (SLR) method equipped with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, this method involves searching, filtering, and analyzing literature from reliable sources to compile a comprehensive theoretical framework. Based on the simulation of circular slit diffraction using matlab application with the same wavelength and different radii of the circle, it shows that the larger the radius of the circle will produce a narrower diffraction pattern, while the smaller the radius of the circle will produce a wider diffraction pattern. Meanwhile, when using the same radius and different wavelengths, it shows that longer wavelengths produce wider diffraction patterns, while shorter wavelengths produce narrower diffraction patterns.